2021
DOI: 10.3389/fcell.2021.654559
|View full text |Cite
|
Sign up to set email alerts
|

Dental-Derived Mesenchymal Stem Cells: State of the Art

Abstract: Mesenchymal stem cells (MSCs) could be identified in mammalian teeth. Currently, dental-derived MSCs (DMSCs) has become a collective term for all the MSCs isolated from dental pulp, periodontal ligament, dental follicle, apical papilla, and even gingiva. These DMSCs possess similar multipotent potential as bone marrow-derived MSCs, including differentiation into cells that have the characteristics of odontoblasts, cementoblasts, osteoblasts, chondrocytes, myocytes, epithelial cells, neural cells, hepatocytes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 227 publications
(229 reference statements)
1
54
0
Order By: Relevance
“…Moreover, the secretion of cytokines IL-6 and TNF-α, combined with trophic factors, enhances immunoregulation and reverts the damage to host neurons. Collectively, the published reports indicated that the hDPSC- and SHED- conditional medium can be effective in neurogeneration of damaged neuron tissue [ 35 , 102 , 115 , 116 ].…”
Section: Dscs Secretome In Central Nerve System Diseases Therapymentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, the secretion of cytokines IL-6 and TNF-α, combined with trophic factors, enhances immunoregulation and reverts the damage to host neurons. Collectively, the published reports indicated that the hDPSC- and SHED- conditional medium can be effective in neurogeneration of damaged neuron tissue [ 35 , 102 , 115 , 116 ].…”
Section: Dscs Secretome In Central Nerve System Diseases Therapymentioning
confidence: 99%
“…As an alternative solution in regenerative medicine or tissue engineering, the application of MSCs offers a wide range of therapeutic possibilities [ 134 , 135 ]. A majority of reports utilized an exogenous, autologous, or allogeneic MSC delivery into the injury site [ 9 , 35 , 42 , 56 , 59 , 60 , 116 , 136 ]. However, other studies attempted to recruit endogenous MSCs through the administration of the bioactive molecules released by BMMSCs, which may activate or inhibit different signaling pathways, enhancing the regeneration of bone defects [ 136 , 137 ].…”
Section: Dental Mscs-cm In Tissue Regenerationmentioning
confidence: 99%
See 3 more Smart Citations